ANALISIS HAMBATAN GURU DALAM MENGAJARKAN VOLUME KUBUS DI KELAS V SDN 102 KOTA BENGKULU - Melysyah Ihsani; Siti Fatimah; Neza Agusdianita (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the obstacles experienced by teachers in teaching the volume of a cube to fifth-grade students at SDN 102, Bengkulu City. This study used a descriptive qualitative method, with data collection through semi-structured interviews with class teachers. The results indicate several major obstacles in the learning process. These obstacles include students' poor mastery of multiplication operations as a prerequisite for calculating the volume of a cube, students' difficulty in understanding the abstract concept of space, and the limited use of concrete media that can facilitate visualization of the concept of geometric shapes. Furthermore, teachers face challenges in adapting learning strategies to the variety of student learning styles, resulting in uneven student engagement and understanding. These obstacles result in slow learning and students' poor ability to apply volume formulas correctly. This study emphasizes the need for the use of concrete and digital media, reinforcement of basic concepts, and the application of more varied and contextual learning methods to significantly improve students' understanding of the concept of volume of a cube.